Frequency-Tunable Coherent THz-Wave Pulse Generation Using Two Cr:Forsterite Lasers with One Nd:YAG Laser Pumping and Applications for Non-Destructive THz Inspection - Tanabe, Tadao; Oyama, Yutaka (IntechOpen, 2011)
None